FACTORS INFLUENCING ADOPTION OF RECOMMENDED SOYBEAN-MILK PROCESSING TECHNOLOGY AMONG WOMEN PROCESSORS IN ZARIA AND MAKARFI LGAs OF KADUNA STATE, NIGERIA - Saddiq, N.M.; Casmir, R.; Shehu, A. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
This paper assessed the socio-economic factors influencing the adoption of Soybean-milk processing technology and the level of adoption among women processors. A multi-stage sampling technique was adopted for this research. A total number of 170 women were trained from two LGAs and the same number was purposively selected as the sample size of the study. Data were collected through the use of a structured questionnaire and both descriptive and inferential statistics were used to analyse the data. The results indicated that most (91.8%) of the processors had adopted Soybean-milk processing practices. The result of the Tobit regression analysis showed that marital status (β = 0.0266), processing experience (β = 0.0429), number of extension contact (β = 0.0265), and membership of association (β = 0.0286) were positive and significant in influencing the adoption of Soybean processing technology at 10%, 1%, and 5% levels of probability respectively. Therefore, the null hypothesis (Hoi) was rejected. The study concluded that the adoption of Soybean-milk processing technology had a significant effect on the livelihood of women processors with increased income and change in their level of living. Therefore it was recommended that since there was significant effect on the livelihood of women processors government, non-governmental organizations and other relevant institutions should provide a more enabling environment; this could be done by providing a link to market for more production, more training and workshops for better packaging, as well as increased product’s shelf life in order to motivate adopters’ engagement and mobilize more processors all of which could ensure more rapid adoption of the technology among processors.